THE STATE OF PSYCHOLOGICAL READINESS OF PRIMARY SCHOOL TEACHERS TO INCLUSIVE EDUCATION - Kipichenko, Natalia; Gurskaya, Alevtina (Educological discourse, 2018)
The article describes the state of psychological readiness of primary school teachers for the introduction of inclusion into the national education system. The 92,8% of pedagogical workers have been found to support the latest changes regarding inclusive education. The above points testify to the humanistic orientation of teachers to the organization of educational process involving the children with special needs. They perceive and appreciate not only the positive qualities of the students, but the person as a whole, that is, respect their dignity, recognize the right to free access to education. At the same time, the desire to work with this category of children was revealed by only 6,98% of the respondents. Reasons that prevent teachers from perceiving educational reforms, lack of information about working with special children (87,21%), lack of understanding how and how to make individual programs for children with special educational needs and implement an algorithm for its implementation (94,77%). There is also a fear of preserving the life and health of such students (97,09%), as experience proves that children with emotional and intellectual disorders do not always control their actions and threaten not only their personal health and life, but also other children. Proposals have been developed to increase the teachers’ readiness to work with children with special educational needs. It is important to clearly identify the category of children with special educational needs that are able to integrate into society and minimize the individual curriculum. The future teachers need to know articles of the Law "On Education", which define the requirements for inclusive classes. It is necessary to hold trainings, master classes, consultations, round tables, webinars on problems of inclusive education for teachers. It’s important to involve in the development of individual programs for children with special educational needs of defectologists, speech therapists, special correctional teacher.